2013
DOI: 10.1097/mph.0b013e3182841574
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Vertebral Fractures in Adolescents and Young Adults With Thalassemia Syndromes

Abstract: Osteoporosis is a common problem in thalassemics. As the most affected bone is spinal vertebrae, theoretically, it should have the greatest risk of fracture. However, vertebral fracture (VF) in thalassemics was rarely reported. Screening for asymptomatic VF in thalassemics has not been reported. We, therefore, evaluated prevalence of VF in adolescents and young adults with thalassemia. A total of 150 patients with thalassemia, aged 10 years and older were enrolled. Lateral thoracolumbar spine radiography was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…The prevalence of thalassemia-associated osteoporotic fractures in beta-thalassemia major and in the various thalassemia syndromes has not been well established This study demonstrated that the prevalence of vertebral fracture was 16.3% (14/86), which was comparable with a previous study by Engkakul et al, which reported that the prevalence of vertebral fracture was 13% in Thai patients with thalassemia [ 26 ] The prevalence of vertebral fractures in the present study, however, was slightly higher than that in a previous report from a large cohort study including 31 clinical centers in the United States, Canada, and the United Kingdom (16.3% vs. 10.6%) [ 21 ]. The discrepancy in prevalence among the studies might be explained by three main factors including (i) the differences in the diagnostic methods of vertebral fracture because in the previous study, fractures were assessed by the self-reported fracture history questionnaires, but in this cohort, vertebral fractures included both symptomatic and/or radiographic vertebral fractures; (ii) the enrolled subjects in this study were adult patients with a high iron burden, and about 20% of patients had iron-associated endocrinopathies.…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of thalassemia-associated osteoporotic fractures in beta-thalassemia major and in the various thalassemia syndromes has not been well established This study demonstrated that the prevalence of vertebral fracture was 16.3% (14/86), which was comparable with a previous study by Engkakul et al, which reported that the prevalence of vertebral fracture was 13% in Thai patients with thalassemia [ 26 ] The prevalence of vertebral fractures in the present study, however, was slightly higher than that in a previous report from a large cohort study including 31 clinical centers in the United States, Canada, and the United Kingdom (16.3% vs. 10.6%) [ 21 ]. The discrepancy in prevalence among the studies might be explained by three main factors including (i) the differences in the diagnostic methods of vertebral fracture because in the previous study, fractures were assessed by the self-reported fracture history questionnaires, but in this cohort, vertebral fractures included both symptomatic and/or radiographic vertebral fractures; (ii) the enrolled subjects in this study were adult patients with a high iron burden, and about 20% of patients had iron-associated endocrinopathies.…”
Section: Discussionsupporting
confidence: 81%
“…Extremity fractures are the most common (26), in particular at the upper extremity (31). Vertebral fractures are usually underestimated, and their prevalence varies from 2.6% to 13% (26,36).…”
Section: Bone Metabolism In Tm Patientsmentioning
confidence: 99%
“…Multiple and recurrent fractures were sustained on mild and moderate trauma as reported previously as well [19,20]. Asymptomatic vertebral fractures have been reported in thalassemia in patients above 20 years of age [21]. There is a prevalence of 40-80% demineralization of lumbar spine [22,23] associated with back ache in thalassemia [23].…”
Section: Discussionmentioning
confidence: 58%